2015
DOI: 10.1021/acsnano.5b05984
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of Redox-Induced Fe–N Switching Behavior as a Determinant Role for Oxygen Reduction Activity

Abstract: The commercialization of electrochemical energy conversion and storage devices relies largely upon the development of highly active catalysts based on abundant and inexpensive materials. Despite recent achievements in this respect, further progress is hindered by the poor understanding of the nature of active sites and reaction mechanisms. Herein, by characterizing representative iron-based catalysts under reactive conditions, we identify three Fe-N4-like catalytic centers with distinctly different Fe-N switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
587
2
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 559 publications
(662 citation statements)
references
References 58 publications
62
587
2
11
Order By: Relevance
“…The appearance of the molybdate (PMo 12 ) redox transitions at more positive potentials relative to those characteristic of the Co(II)/(III) redox couple may explain higher activity toward oxygen reduction of the systems containing PMo 12 O 40 3− together with cobalt porphyrin in comparison to pure CoPPIX [33]. The similar electrocatalytic enhancement effect has been postulated for the pyrolyzed FeNx catalyst co-existing with metallic centers characterized by redox processes existing at the relatively more positive potentials [34]. Furthermore, it is reasonable to expect that gold nanostructures acting as the powerful hydrogen peroxide reduction catalyst induce the second step in the oxygen reduction mechanism: reductive decomposition of hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 71%
“…The appearance of the molybdate (PMo 12 ) redox transitions at more positive potentials relative to those characteristic of the Co(II)/(III) redox couple may explain higher activity toward oxygen reduction of the systems containing PMo 12 O 40 3− together with cobalt porphyrin in comparison to pure CoPPIX [33]. The similar electrocatalytic enhancement effect has been postulated for the pyrolyzed FeNx catalyst co-existing with metallic centers characterized by redox processes existing at the relatively more positive potentials [34]. Furthermore, it is reasonable to expect that gold nanostructures acting as the powerful hydrogen peroxide reduction catalyst induce the second step in the oxygen reduction mechanism: reductive decomposition of hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 71%
“…Furthermore, the nature of the active sites is still strongly debated. Different views conflict with each other and for example, some authors reported that iron species coordinated with nitrogen in various configuration referred as FeN x or FeN x C y are mainly responsible for the electrochemical activity [47][48][49], while others showed that iron-free electrocatalysts with C x N y sites have significant activity [50,51]. Furthermore, recently, the ORR activity of iron based (Fe 3 C) core-shell particles in which no nitrogen atoms are incorporated in the carbon shell was also reported [52].…”
Section: Discussionmentioning
confidence: 99%
“…5,[10][11][12][13][14][15][16][17][18] To date, three types of active sites have been shown to exhibit decent ORR activity in acidic media: metal-nitrogen moieties embedded in carbon (denoted as MN x C y ), 9,11,14,16,18,19 nitrogen-carbon moieties (denoted as N x C y ), 20,21 and nitrogen doped carbon encapsulating inorganic metal species (denoted as M@N x C y ). 5,[10][11][12][13][14][15][16][17][18] To date, three types of active sites have been shown to exhibit decent ORR activity in acidic media: metal-nitrogen moieties embedded in carbon (denoted as MN x C y ), 9,11,14,16,18,19 nitrogen-carbon moieties (denoted as N x C y ), 20,21 and nitrogen doped carbon encapsulating inorganic metal species (denoted as M@N x C y ).…”
Section: Introductionmentioning
confidence: 99%